Paradigma Integratif Pendidikan Islam sebagai Modal dalam Menghadapi Era 4.0 - Marzuki Marzuki; Halimatun Sakdiyah (Pascasarjana IAIN Sultan Amai Gorontalo, 2023)
This study is entitled the integrative paradigm of Islamic education as capital in facing the 4.0 era. This type of qualitative research, the category of library research, uses historical, comparative, and educational science approaches. The method is descriptive and analytical. Studies prove that the integrative paradigm is the basic capital of Islamic education in facing the 4.0 era without having to escape identity as an Islamic educational institution that has characteristics and adheres to the principles of al-muhafadhah 'ala al-qadim ash-shalih wa al-ahdzu bi al-jadid alashlah, namely maintaining the Islamic religious tradition by steadfastly preserving its myriad treasures and without having to lose the function of Abdullah and his caliphate or empirical rationale towards spiritual empirical rationality by integrating several paradigms namely non-dichotomous Education, From Teaching to Learning, Novum Organum to Tartium Organum, as well as from the profession to the prophetic. In this way, Islamic education will leave the point of absurdity of civilization towards an advanced civilization, even if the students have IQ Intellectual intelligence, EQ emotional intelligence, and SQ spiritual intelligence with these three bits of intelligence, so students become rahmatan lil alamin.